The Development and Validation of a Scale to Measure Reproductive and Sexual Health of Young Women in the Colombian Caribbean Region [Construcción y Validación de Una Escala Para Evaluar Salud Sexual y Reproductiva en Adolescentes Mujeres de la Región Caribe Colombiana] - Vera-Villarroel, P; Pavez-Salinas, P; Celis-Atenas, K (Pontificia Universidad Javeriana, 2016)
This article describes the design and validation of a scale for evaluating reproductive and sexual health. 919 young females from 11 to 19 years in five Caribbean- Colombian cities were administered the questionnaire that assesses attitudes and subjective norms about the reproductive sexuality, based on the planned behavior theory (Ajzen & Fishbein, 2000). The reliability and validity of the instrument was analyzed through exploratory factorial analysis with principal components and VARIMAX rotation. The methodology includes two independent studies; in study 1 (pilot test) the first questionnaire consisted of 172 items and decreased to 78 in the final sample. For study 2, the attitude scale reported (Mean = 3.68, ED = 1.21) and Cronbach s alpha reliability was 0.91. Two factors were extracted and grouped into two dimensions that explain 67.10% of the variance. For the subjective norms scale (Mean = 3.8, ED = 1.1) Cronbach s alpha reliability was 0.97 and eleven factors were extracted and grouped into nine dimensions, which explain 75.89% of the variance. The scale showed good reliability and structural stability for the analysis and design of programs for sexual and reproductive health in adolescent girls.